2018
DOI: 10.3390/rs10020274
|View full text |Cite
|
Sign up to set email alerts
|

Using High-Resolution Airborne Data to Evaluate MERIS Atmospheric Correction and Intra-Pixel Variability in Nearshore Turbid Waters

Abstract: Abstract:The implementation of accurate atmospheric correction is a prerequisite for satellite observation and water quality monitoring in coastal areas. The potential of the fast-line-of-sight atmospheric analysis of spectral hypercubes (FLAASH) was investigated here for the medium resolution imaging spectrometer (MERIS). As the comparison between discrete field sampling points and macro-scale satellite pixels is subject to spatial biases associated with small-scale spatial patchiness in the turbid and highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…This is corroborated by comparing in situ SSC data for the two campaigns, where mean SSC in November was nearly twice than that in January 2018 (i.e., 75.8 versus 46.4 mg/L in Table 2). The ρw are characteristic of highly turbid waters and are similar in shape and magnitude to previously reported spectra [7,49,50], with distinct increased water-leaving radiance within the red/NIR region, i.e., 650 to 670 nm. The higher variability in the spectral curves in Figure 3a within the 600-700 nm range reflects a larger variability in optically active constituents of the river waters in the wet season (prior to November) than in the dry season (after November).…”
Section: In Situ Radiometry and Sscsupporting
confidence: 82%
“…This is corroborated by comparing in situ SSC data for the two campaigns, where mean SSC in November was nearly twice than that in January 2018 (i.e., 75.8 versus 46.4 mg/L in Table 2). The ρw are characteristic of highly turbid waters and are similar in shape and magnitude to previously reported spectra [7,49,50], with distinct increased water-leaving radiance within the red/NIR region, i.e., 650 to 670 nm. The higher variability in the spectral curves in Figure 3a within the 600-700 nm range reflects a larger variability in optically active constituents of the river waters in the wet season (prior to November) than in the dry season (after November).…”
Section: In Situ Radiometry and Sscsupporting
confidence: 82%
“…Species niche habitat distribution mapping) remote sensing applications is the effectiveness of the AC applied to the EO data. In turbid coastal waters, standard AC models often exhibit large inaccuracies (Fan et al 2017) and previous studies have shown that not one single AC works in all cases (e.g., Larnicol et al 2018;M. Zhang et al 2018).…”
Section: Supporting the Delivery Of International Conventions Through Eomentioning
confidence: 99%
“…The importance of using high spatial resolution remote sensing data to monitor coastal and wetland areas is shown in [6][7][8][9][10]. Abascal Zorrilla et al [6] highlight the benefit of high spatial resolution satellite data for monitoring the dynamics of subtidal mudbanks along the coasts of French Guiana.…”
mentioning
confidence: 99%
“…Wang et al [7] present and apply a new method to classify coastal wetland vegetation using high spatial resolution imagery. Larnicol et al [8] use high-resolution airborne data to evaluate the validity of MERIS atmospheric correction and study intra-pixel variability in nearshore turbid waters. Pan et al [9] apply a fusion method to Landsat-8/OLI and GOCI satellite data for hourly and high spatial resolution mapping of suspended particulate matter in the Yangtze (Changjiang) Estuary.…”
mentioning
confidence: 99%